A Review of Open Access, No-Fee Journals Indexed in PubMed and Scopus for Publishing Image Reports in Medical Research - Gaggero, Gabriele (Acta medica Lituanica, 2024)
Background: Aspects of medicine can be conveyed through paradigmatic images (anatomical-surgical, radiological, microscopic) in image reports, a type of article more immediate than case reports. The aim of this review is to find journals allowing the publication of image reports and that are free of charge, open access and indexed in the best databases.Methods: The search started with a Boolean string and followed the PRISMA 2020 guidelines. Eligibility criteria were: English language, human medicine field, international DOI and ISSN codes applied, free of charge, open access, PubMed/Scopus indexed.Results: 15,504,000 items were retrieved; 102 met all criteria. Instructions to authors were screened to extract journals that allowed image reports: 39 (39/39 Scopus-indexed; 29/39 PubMed-indexed). Most were in oncology (6/39) and general medicine (5/39), followed by neuroscience, fetal/pediatric and nephrology (4/39 each), urology, dermatology, hematology (3/39 each), thoracic/pleural/peritoneal diseases (2/39), and finally endocrinology, cytology, rheumatology, ophthalmology, gastroenterology (1/39 each). 21/39 allowed a single image; word count ranged from 100 to 1500. 32/39 reported a maximum number of references (range: 0–20), while 15/39 reported a maximum number of authors (range: 2–6).Conclusions: Compared to the vast publishing landscape, there are very few English-language, open access, PubMed/Scopus-indexed medical journals that allow free of charge publication of image reports. The majority are in the fields of oncology and general medicine, but other specialties are also represented. Image reports are usually articles with a limited number of words, references and authors allowed, as their purpose is much more a practical/didactic take-home message rather than a broad research with many authors. The review shows that image reports, still important for their educational value in medical knowledge transfer, are freely publishable and consultable in journals with international visibility.